Comparison of Role of Colposcopic Directed Biopsy Versus Cytology In Screening of Pre Invasive Lesions and Early Detection of Cervical Cancer - A., Vijay; Nath, J.D.; Deka, N. (International Journal of Medical Research and Review, 2015)
Introduction: Cancer cervix is the most common malignancy in the developing world and second most common in the world amongst women. The easy accessibility of cervix with newer screening and diagnostic procedures has rendered it a preventable disease. Colposcopic evaluation and guided biopsy is an important diagnostic step and standard of management for abnormal cytological smear. Methods: A cross sectional study of a total of 50 patients attending gynecology OPD in Gauhati Medical College and Hospital was conducted between July 2013 & June 2014. Patients between 20-60 years were included. PAP smear, Colposcopy and Colposcopic directed Biopsy were taken from the suspicious areas. Results: On cytology 24% cases (12/50) were neoplastic. On colposcopy 28% cases (14/50) were neoplastic though on histopathology 50% cases (25/50) were neoplastic. Sensitivity, specificity, positive predictive value and negative predictive value for PAP smear was 24%, 76%, 50% and 50% respectively. Sensitivity, specificity, positive predictive value and negative predictive value for colposcopy was 40%, 84%, 71% and 58% respectively. Conclusion: For screening and detection of cervical lesions combination of various methods should be employed which will increase diagnostic accuracy.